Transitional organisations, affective atmospheres and new forms of being‐in‐common: Post‐disaster recovery in Christchurch, New Zealand. Issue 3 (2nd May 2018) - Cloke, Paul; Conradson, David
Abstract : With reference to the post‐disaster urban landscape of Christchurch, New Zealand, this paper examines the emergence of particular forms of nongovernmental organisation after the 2010 and 2011 earthquakes, and the kinds of transitional activities in which they have been engaged. Two sets of conceptual apparatus are deployed. First, we suggest that the spaces and activities of transitional organisations have provoked particular "affective atmospheres" in Christchurch that are informing new senses of place, belonging, imagination and social encounter. Second, and drawing on ideas from poststructural geographies of ethics, we suggest that transitional organisations in Christchurch have assembled a capacity for new forms of "being‐in‐common", and in so doing are facilitating new and more positive emotional performances in the city. The paper thereby contrasts the neoliberal affects inherent in top‐down plans for rebuilding the city centre in Christchurch with the affective atmospheres emerging from the activities of these transitional organisations. We also acknowledge the potential in these transitional activities for new forms of incommonness, arising from and at the same time contributing to the unfolding geographies of the post‐disaster city.